2022
DOI: 10.3389/fmicb.2021.793050
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Gut Microbiota and Infections During Early Childhood

Abstract: Gut microbiota composition during the first years of life is variable, dynamic and influenced by both prenatal and postnatal factors, such as maternal antibiotics administered during labor, delivery mode, maternal diet, breastfeeding, and/or antibiotic consumption during infancy. Furthermore, the microbiota displays bidirectional interactions with infectious agents, either through direct microbiota-microorganism interactions or indirectly through various stimuli of the host immune system. Here we review these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 254 publications
(269 reference statements)
0
15
0
Order By: Relevance
“…The gut microbiota composition during infancy or early childhood is variable, dynamic, and influenced by both prenatal and postnatal factors [80]. Many studies have shown that intestinal viral infections may be associated with severe illness such as hemorrhagic enteritis and even necrotizing enterocolitis (NEC) [17,18,81,82].…”
Section: Necrotizing Enterocolitismentioning
confidence: 99%
See 1 more Smart Citation
“…The gut microbiota composition during infancy or early childhood is variable, dynamic, and influenced by both prenatal and postnatal factors [80]. Many studies have shown that intestinal viral infections may be associated with severe illness such as hemorrhagic enteritis and even necrotizing enterocolitis (NEC) [17,18,81,82].…”
Section: Necrotizing Enterocolitismentioning
confidence: 99%
“…Although studies mentioned previously indicated an episodic association of enteric viruses in NEC, one study by Skeath et al [83] in 2016 for 17 NEC infants without detection of any related viruses may suggest that viral etiology is unlikely to be causative for most sporadic forms of NEC. Understanding of the mechanisms in microbiota-immunity-infectious agent axis is necessary to define potential preventive or therapeutic tools against significant infections in children [80].…”
Section: Necrotizing Enterocolitismentioning
confidence: 99%
“…and pro-inflammatory microbiome metabolic pathways may partly explain the sustained reductions in child mortality due to diarrhea and dysentery observed in those settings [ 111 113 ]. Gut microbiota composition is associated with both increased and reduced severity of enteric infections [ 114 ]. Limited evidence suggest that better or worse enteric infection outcomes may vary by microbiota composition and pathogen [ 114 ].…”
Section: Main Textmentioning
confidence: 99%
“…Gut microbiota composition is associated with both increased and reduced severity of enteric infections [ 114 ]. Limited evidence suggest that better or worse enteric infection outcomes may vary by microbiota composition and pathogen [ 114 ]. For example, mixed diarrheagenic E. coli and viral infections in children were associated with increased Bifidobacterium spp.…”
Section: Main Textmentioning
confidence: 99%
“…4 In addition, it has been postulated that intestinal and respiratory dysbiosis has a role in respiratory infections and airway obstruction. 5,6 Dysbiosis can promote inflammatory pathways and impair immune defense against pathogens. 7 Probiotics are "live microorganisms which confer a beneficial effect on the host."…”
mentioning
confidence: 99%